2009
DOI: 10.1097/jnr.0b013e3181a53f82
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Depression During Menopause

Abstract: The purpose of this study was to survey the prevalence of women's depression during menopause and investigate the relationships between menopause depression and variables including self-concept, menopause attitudes, life-event stresses, climacteric physiological symptoms, and demographics. Research was conducted using a cross-sectional study and self-administered questionnaires. We randomly selected female participants between the ages of 45 and 55 years from Tainan City in southern Taiwan using the cluster me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…This finding was consistent with previous studies (Lu, Tseng, Lin, Luh, & Shu, 2009;Sung, 2006). This finding was consistent with previous studies (Lu, Tseng, Lin, Luh, & Shu, 2009;Sung, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with previous studies (Lu, Tseng, Lin, Luh, & Shu, 2009;Sung, 2006). This finding was consistent with previous studies (Lu, Tseng, Lin, Luh, & Shu, 2009;Sung, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…42,47,48 Finally, it is also likely that the diminished quality of life experienced by women suffering from frequent and severe hot flashes causes an increase in depression, thus indirectly impacting cognitive performance. 49…”
Section: Hot Flashes and Cognitive Impairmentmentioning
confidence: 99%
“…A cross-sectional study (Wang, Booth-LaForce, Tang, Wu, & Chen, 2013) with 566 women in Southern Taiwan suggested that depressive symptoms tended to be affected by chronic disease, while another study conducted in 266 women also from Southern Taiwan (Lu, Tseng, Lin, Luh, & Shu, 2009) found no significant relation between chronic disease status and depressive symptoms. Income was regarded as a risk factor associated with depressive symptoms in some studies (Unsal, Tozun, & Ayranci, 2011).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In contrast, Timur and Sahin (2010) found a positive correlation. However, most studies have shown no significant relation between age and depressive symptoms (Brown, Gallicchio, Flaws, & Tracy, 2009;Lu et al, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%